The Co-evolution of Corporate Philanthropy and Stakeholder Responses in China - WAN, Guoguang (Institutional Knowledge at Singapore Management University, 2015)
The study examines the effect of sudden natural disasters on the co-evolution of corporate philanthropy and stakeholders¡¦ responses to it. We argue that sudden events facilitate the institutionalization process of corporate philanthropy, which lead to an overall increase in corporate philanthropic behaviors. Meanwhile, as corporate philanthropy becomes more legitimate, stakeholders gradually shift attention away from the philanthropic act itself to more individualized, firm-specific features related to philanthropy. As a result, stakeholders¡¦ responses to corporate philanthropic activities become less positive in general, resulting in a weaker relationship between corporate philanthropy and firm value. But for firms that could demonstrate genuineness in their philanthropic donations, stakeholder responses remain positive. Using the Wenchuan earthquake which occurred in 2008 in China as a sudden event and analyzing data from 2,318 Chinese listed firms between year 2004 and 2012, we find support for these arguments. These findings have implications for strategy and policy.